SISTEM INFORMASI PESAN ANTAR MAKANAN BAGI UMKM KULINER YOGYAKARTA - , CICHI EFRILINA; , Mardhani Riasetiawan, S.E., Ak., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Food delivery order is usually made by the busy people. This rush of people often forces themselves to fulfill their daily meal instantly through the food delivery order service. Thus, people tend to order the fast-food. However, the limited information about the list of restaurant arouses a problem for the costumers. The system of food delivery order is aimed to facilitate the costumers in ordering the food. This system is integrated with the database server to display the menu in detail and enable the costumers in choosing the menu directly. This system has an advantage point in choosing food based on the location and category by using map. Therefore, the costumers will be easier to reach the culinary location in Yogyakarta The system is developed by using the data base of MySQL and the programming language of PHP with the framework of CodeIgniter. This system has an ordering. service feature, location and category searching, shopping chart and data management such as data of menu, data of member, data of order and a feature which display the monthly and yearly graphic of order food delivery.